(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
Professional training in a foreign language, which involves the development of communicative competence, should be carried out on the basis of certain principles, requirements and rules that take into account the needs of the student, the goals and objectives of the educational process. Another important condition for this process is a correctly selected set of exercises and tasks. This article analyzes some types of exercises aimed at the systematic development of speech activity.